Increasing the capacity of health cadres to prevent and self-management of Osteoarthritis - Arifin Triyanto; Heny Suseani Pangastuti; Diana Nurlita; Anisah Umami (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Osteoarthritis (OA) is a clinical syndrome characterized by joint pain with varying degrees of functional limitations that impact quality of life. Data in Indonesia shows that the national prevalence of osteoarthritis is 7.3%. Several factors in the high prevalence of OA that can be modified require lifestyle modification to prevent OA. Self-management in OA can help maintain the individual's functional capacity, improve self-image, and improve the quality of life of the patients. This community service is health education for health cadres and the general public over the age of 35 years in one of the areas in Godean, Sleman, Yogyakarta. The team measured the level of participants' knowledge about osteoarthritis and self-screening for osteoarthritis in community service. Results obtained the majority of respondents were in the mild osteoarthritis category (36.5%). The results of the respondents' knowledge scores were the difference in average knowledge before and after providing education, there was an increase in knowledge scores of 17.87. Providing health education can increase public knowledge about osteoarthritis before and after health education about prevention and self-management of osteoarthritis.